A rare case of basal cell adenoma in the alveolus of the anterior maxilla. Issue 2 (March 2022) - Takeuchi, Shin; Yamano, Yukio; Toeda, Yuriko; Kita, Akihiro; Uzawa, Katsuhiro
Abstract: Basal cell adenoma (BCA) is classified in benign salivary gland tumors by WHO in 1991. Incidence rate of BCA is 1.0 %–3.7 % of all salivary gland tumors. BCA tend to occur in parotid glands and those of minor gland origin is rare. We present a case of BCA of minor salivary gland in the alveolus of the anterior maxilla. A 41-year-old man was referred to our department because of a swelling in the left alveolus of the anterior maxilla. On the basis of clinical findings, the diagnosis was a benign tumor of the alveolus of the anterior maxilla and the tumor was removed under general anesthesia. The tumor was well-defined, no invasion of surrounding tissue, and was easily resected. Immunohistochemically, tumor cells showed positive reaction for S-100 protein, cytokeratin (AE1/AE3), p40, vimentin and epithelial membrane antigen (EMA). On the contrary, Ki-67 labeling index that is said to be an indicator of malignancy was low. Thus, the tumor diagnosed BCA. One year and six months have passed from the operation, there is no sign of recurrence and metastasis.